PELATIHAN MARKETING ONLINE DALAM MENGHADAPI NEW NORMAL DI DESA TANJUNGTANI, KECAMATAN PRAMBON, KABUPATEN NGANJUK - Imam Basthomi (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
In early 2020 all countries were affected by Corona virus outbreak (Covid-19). That virus spread fastly so World Health Organization (WHO) announced Pandemic emergeny status. Indonesia government use Physical Distancing, Social Distancing, and Rapid Test to reduce spreading of covid-19. They also instructed their inhabitant to carry out the work from home, study from home, and pray from home programs. The efforts to prevent the transmission of Covid-19 has an impact on various fields, one of them in economic sector. Based on that statement, KKN 144 of UIN Sunan Kalijaga Yogyakarta grup that doing dedication in Tanjuntani Village, Prambon District, Nganjuk Regency hold an Online Marketing Training. The training is intended for businessmen or UMKM and youth in Tanjungtani Village. Aim of that training is to maintain economic condition in there. The dedication method use observation, aproach, interview, and socialization. The result of these activities indicate that businessmen or UMKM have the potential to develop their businesses by aplying Online Marketing knowlegde. By utilizing technology, the impact of covid-19 on economic sector can be reduced.